Accumulation Detection of Cadmium in some land-use soil of Baghdad city, Iraq - Fadhel, Mena Amer; Abdulhussein, Firas Mudhafar (Iraqi Journal of Science, 2022)
This study aims to detect cadmium accumulation in the soil of Baghdad. Twenty soil samples were collected randomly during November 2020 to cover the study area, emphasizing the nature of each area (agricultural, commercial, industrial, residential, roadside, and waste dumping sites). All soil samples were subjected to geochemical analysis using atomic absorption spectrometry (ASS) to determine the concentration of cadmium in Baghdad soil. The laboratory data was utilized to design the spatial analysis map using Arc GIS 10.4.1 to investigate the spatial distribution of cadmium. The results demonstrated that the total content of cadmium in the study area ranged from 0.121to 1.78 mg/kg. All results of cadmium concentrations are within the allowable limits of WHO (3 mg/kg), and the mean concentration of cadmium according to the type of land use is shown by the following decreasing order: roadside > agricultural areas > residential areas > industrial areas >waste dumping site> commercial. In addition, the spatial analysis map showed the accumulation of cadmium concentration on the Al-Karkh side than on the Al-Rissafa side of Baghdad city. A comparison between cadmium concentration in the soil of some land- use for the current study and cadmium concentration in previous studies showed that the concentration of cadmium decreased from previous years, except roadside sites recorded a higher cadmium concentration than the cadmium concentration of roadside areas according to [12].